GE_GERICHTE P/23593/2024 vom 19. November 2024 - GE Cour de justice (2024)
DÉTENTION PROVISOIRE;PROPORTIONNALITÉ;RISQUE DE COLLUSION;RISQUE DE RÉCIDIVE;CASIER JUDICIAIRE;RADIATION(EFFACEMENT) | CPP.221; CPP.197; CPP.212; CP.369; LCJ.34